Evaluation of children 8 -9 years old based on their physical abilities - Antonakopoulou, S.; Mavvidis, A.; Pilianidis, T. (Biology of Exercise, 2009)
This research deals with four basic abilities of two different samples. One group of 267 selected subjects, among a larger sample of 8 to 9 year old children and one of 211 non-selected. The target of the research was to evaluate the basic abilities, speed at 30 meters, endurance at speed with change of direction, jumping ability and throwing ability; furthermore, to found out the differences of performance among the two sexes at this age, separately for each sample; finally, to correlate the abilities of lower extremities that arise from the application of tests, with those of strength velocity at upper extremities, separately for boys and girls at selected and non selected subjects. Differences were examined with the one-way ANOVA, while the correlation was carried out by Pearson coefficient. Performances of boys of this age (8 - 9 years old) are statistically better than those of girls at all abilities measured in non-selected children (p .001). However, in selected ones, the differences were smaller, mainly at speed the 70 meters from the standing position (p .0001) and throwing strength velocity at upper extremities, as well as strength of vertical jump, at p .05, while no difference was observed at speed with change of direction at both sexes. Strength velocity at upper extremities is correlated to the basic abilities of lower extremities more in non-selected children.